2004
DOI: 10.1002/ana.10831
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of atypical absence seizures

Abstract: A time course study that examined the effects of the female estrous cycle on the chronic slow spike-and-wave discharges (SSWDs), gamma-aminobutyric B receptor (GABA(B)R) binding, and GABA(B)R protein expression was conducted in Long Evans hooded rats treated during development with a cholesterol synthesis inhibitor AY9944 (AY). In addition, a pharmacological study using the hormones progesterone, 17 beta-estradiol, mifepristone (intracellular progesterone receptor antagonist), tamoxifen (intracellular estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Chronic slow spikeand-wave discharges (SSWDs) induced by the cholesterol synthesis inhibitor AY9944 in Long Evans rats were exacerbated by the administration of both progesterone and allopregnanolone. This effect was not blocked by mifepristone 141 .…”
Section: Progesterone and The Central Nervous Systemmentioning
confidence: 73%
“…Chronic slow spikeand-wave discharges (SSWDs) induced by the cholesterol synthesis inhibitor AY9944 in Long Evans rats were exacerbated by the administration of both progesterone and allopregnanolone. This effect was not blocked by mifepristone 141 .…”
Section: Progesterone and The Central Nervous Systemmentioning
confidence: 73%
“…Virtually, a number of adaptive changes in specific binding associated with GABA A receptors as well as in density of dopamine receptors was indeed observed following ovariectomy in different brain structures such as striatum and prefrontal cortex [24,25]. The lack of any changes in the basal occurrence of SWDs in OVX females raises doubts whether and in which way ovarian steroids play a role in the regulation of SWDs under resting conditions [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that acute administration of progesterone aggravates the number of absence seizures both in humans [4] and in rats [5][6][7]. It was also shown that this effect is mediated by the neuroactive derivative allopregnanolone known to facilitate GABA A receptor inhibitory function [6].…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy syndromes in general can also be influenced by hormonal background (Persad et al, 2004). Certain syndromes such as juvenile myoclonic epilepsy, generalized tonic clonic activity on waking, benign rolandic epilepsy, photosensitive epilepsy, reading epilepsy and some generalized epilepsy syndromes present during adolescence (or menarche in girls), when levels of sex hormones rise due to puberty (Grϋnewald et al, 1992;Velišková et al, 2010;Velišková and Desantis, 2013).…”
Section: Relationships Between Hormonal States and Seizure Occurrencementioning
confidence: 99%